Expected ozone benefits of reducing nitrogen oxide (NOx) emissions from coal-fired electricity generating units in the eastern United States. (4th March 2017) - Vinciguerra, Timothy; Bull, Emily; Canty, Timothy; He, Hao; Zalewsky, Eric; Woodman, Michael; Aburn, George; Ehrman, Sheryl; Dickerson, Russell R.
ABSTRACT: On hot summer days in the eastern United States, electricity demand rises, mainly because of increased use of air conditioning. Power plants must provide this additional energy, emitting additional pollutants when meteorological conditions are primed for poor air quality. To evaluate the impact of summertime NOx emissions from coal-fired electricity generating units (EGUs) on surface ozone formation, we performed a series of sensitivity modeling forecast scenarios utilizing EPA 2018 version 6.0 emissions (2011 base year) and CMAQ v5.0.2. Coal-fired EGU NOx emissions were adjusted to match the lowest NOx rates observed during the ozone seasons (April 1–October 31) of 2005–2012 (Scenario A), where ozone decreased by 3–4 ppb in affected areas. When compared to the highest emissions rates during the same time period (Scenario B), ozone increased ∼4–7 ppb. NOx emission rates adjusted to match the observed rates from 2011 (Scenario C) increased ozone by ∼4–5 ppb. Finally in Scenario D, the impact of additional NOx reductions was determined by assuming installation of selective catalytic reduction (SCR) controls on all units lacking postcombustion controls; this decreased ozone by an additional 2–4 ppb relative to Scenario A. Following the announcement of a stricter 8-hour ozone standard, this analysis outlines a strategy that would help bring coastal areas in the mid-Atlantic region closer to attainment, and would also provide profound benefits for upwind states where most of the regional EGU NOx originates, even if additional capital investments are not made (Scenario A). Implications : With the 8-hr maximum ozone National Ambient Air Quality Standard (NAAQS) decreasing from 75 to 70 ppb, modeling results indicate that use of postcombustion controls on coal-fired power plants in 2018 could help keep regions in attainment. By operating already existing nitrogen oxide (NOx ) removal devices to their full potential, ozone could be significantly curtailed, achieving ozone reductions by up to 5 ppb in areas around the source of emission and immediately downwind. Ozone improvements are also significant (1–2 ppb) for areas affected by cross-state transport, especially Mid-Atlantic coast regions that had struggled to meet the 75 ppb standard.